Spirit of the season [large type] - Michaels, Fern (Wheeler Publishing large print hardcover, 2019)
"Joy Preston misses her beloved late grandmother dearly. But when she learns the terms of Nana's will, she's shocked-and more than a little irked. Joy moved to Colorado years ago and is now CEO of a successful nail polish company. Her life and career are in Denver. How can Nana have expected her to give that up, even temporarily, to take over a bed and breakfast in North Carolina for six months? Yet there's no denying Heart and Soul's charm, especially at holiday time. The B&B is always elaborately decorated for the season, with themed guest rooms and dazzling lawn displays created for the annual Parade of Homes competition. The entire town takes part in the festivities, and soon Joy, too, is joining in the gingerbread house contest and letting her reservations melt away. There's another special reason for Heart and Soul's popularity. Rumor has it that, during holiday season, guests can be reunited with the spirit of a loved one who's passed on. Joy's skeptical, yet she feels her beloved Nana's influence all around her . . . perhaps even indulging in a little matchmaking between Joy and handsome estate attorney Will Drake. A special homecoming and the glow of new beginnings will combine to make the holiday magical . . "--